Towards a Circular Economy, Enabling the development of circular products by investigating additional parameters in a profitability mode - Frisk Jonsson, Emilia; Kylin, Jacob (My University, 2024)
The transition towards a circular economy presents both challenges and opportunities for industries worldwide. The European Union is changing the playing field by implementing legislation to ensure access to raw materials, decrease pollution, and secure strategic interests. Additionally, materials necessary for the transition to sustainability are increasing in demand and cost. Navigating this transition requires a comprehensive understanding of circular economy and circular product designs. In the context of the automotive sector, Volvo Group faces the imperative to develop circular products while maintaining profitability. This project aims to investigate in which ways Volvo Group can evaluate and incorporate circularity criteria in their product development process. Identifying and incorporating key parameters that influence profitability calculations for circular projects becomes increasingly important in this transition. The project has been conducted using a combination of a literature study and semistructured interviews, involving product developers and sustainability experts within the automotive industry. Through this combined approach, the study provides Volvo Group with insights necessary for more informed decision-making processes by creating an understanding of the challenges and opportunities associated with transitioning toward a circular economy. The results of this study yield two key parameters, End-of-Life value and Material Supply Chain risk, both of which were deemed crucial for profitability calculations in the context of circular product development within Volvo Group. Additionally, based on the findings, short-term recommendations include further investigation of the proposed parameters. The parameters can assist in navigating the complexities of transitioning towards sustainable and profitable circular product development within the automotive sector.
Keywords: Circular Economy; Circular Product Design; Profitability model; Circular Business Models; End-of-Life Value; Material Supply Chain Risk